an analysis of instructional material and the types of strategies that used for reading 2 course in english education department - ., I Wayan Edi Gunawan; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
ABSTRAK Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk menganalisis relevansi bahan ajar dan jenis strategi pengajaran yang digunakan untuk Membaca 2 kursus dalam bahasa Inggris Departemen Pendidikan. Subyek penelitian ini adalah siswa yang telah diambil Membaca 2 kursus dan dosen yang telah mengajar Reading 2Course dalam bahasa Inggris Departemen Pendidikan. Penelitian ini merupakan penelitian deskriptif kualitatif yang memanfaatkan checklist dan kuesioner. Data yang dikumpulkan dari para juri ahli 'checklist, serta kuesioner dosen dan checklist, dan juga siswa diskusi kuesioner dan focus group. Data yang diperoleh dianalisis secara deskriptif. Temuan penelitian menunjukkan relevansi Bahan Ajar dan Reading 2 silabus dikatakan "Sedikit relevan" untuk digunakan sebagai sumber belajar bahasa Inggris Departemen Pendidikan siswa. Hal ini menunjukkan bahwa semua ahli memilih lebih dari 46% dari kriteria yang telah dicapai. Strategi pengajaran yang sering digunakan di Reading 2 saja wereDiscussion dan Instruksi Langsung. Hasil kuesioner dan diskusi kelompok terfokus dengan siswa dari 9 kelas yang berbeda menunjukkan fokus yang berbeda dari tujuan pembelajaran yang diperoleh oleh siswa dari setiap kelas karena perbedaan materi pembelajaran yang diberikan oleh dosen. Penggunaan strategi pengajaran yang juga tidak memenuhi kriteria pelajar dewasa ini gagal untuk mendorong motivasi siswa belajar. Kata Kunci : Kata kunci: keterampilan membaca, pembaca menengah, bahan ajar, bahan relevansi, dan strategi pengajaran. ABSTRACT This study was a descriptive qualitative research which aimed to analyze the relevance of instructional materials and the type of teaching strategies used for Reading 2 course in English Education Department. The purpose was to describe the relevance of the syllabus and instructional materials, as well as the quality of these learning materials, and to find out the students perception of Reading 2 course. The subjects of this research were the students who have taken Reading 2 course and the lecturer who have taught Reading 2 Course in English Education Department. This research was a descriptive qualitative research which was utilizing checklist and questionnaire. The data collected from the expert judgesâ€™ checklist, as well as lecturer questionnaire and checklist, and also studentsâ€™ questionnaire and focus group discussion. The data obtained were descriptively analyzed. The finding of the research showed the relevance of Instructional Materials and the Reading 2 syllabus was said â€œSlightly Relevantâ€ to be used as learning resource for English Education Department students. It showed that all experts choose more than 46% of criteria which had been reached. The teaching strategies that used frequently in Reading 2 course wasDirect Instruction. The questionnaire result and the focus group discussion with the students from 9 different classes showed different focus of learning objectives acquired by the students of each classes due to the differences of the learning material provided by the lecturer. The use of teaching strategies which also did not meet the criteria of adult learners was failed to encourage studentsâ€™ motivation of learning. keyword : Keywords: reading skill, intermediate reader, instructional materials, relevance materials, and teaching strategies.